ANN based Hybrid Active Power Filter for Harmonics Elimination with Distorted Mains - Laxmi Devi Sahu; Satya Prakash Dubey (Institute of Advanced Engineering and Science, 2012)
The present paper describes dynamic neural network controlled Hybrid Active Power Filter (HAPF) designed for harmonic compensation under variable source/load conditions. A neural network based controller is employed to extract fundamental component of current from non-sinusoidal and unbalanced source currents of the considered supply system. Hybrid filter utilizing the merits of both shunt passive filter and shunt active filter for better compensation performance is applied in this work. Simulation and analysis of three phase hybrid active power filter under balanced and unbalanced load conditions, unbalanced & distorted source conditions have been incorporated using MATLAB/ SIMULINK. The detailed simulation level results have been presented to validate the proposed methodology.Keywords: Hybrid active power filter, THD, Artificial Neural Network Controller, PI controller.DOI: http://dx.doi.org/10.11591/ijpeds.v2i3.276